A New Model of Trapped Charge Sources in Switching Transient Studies in the Presence of Shunt Reactors - Mohsen Akafi-Mobarakeh; Reza Shariatinasab; Pierluigi Siano; Behrooz Vahidi; Hamid Reza Najafi (IEEE Access, 2025)
Insulation coordination studies are of great importance in power grid reliability. In this paper, a new method is proposed for modeling trapped charge sources (TCS) in switching transient studies. The TCS is used to take into account the voltage stored in line capacitors during reclosing operation after fault occurrence. The proposed model is designed based on the active filter concept, thus overcoming the limitations of conventional TCS for simulating transient states in EMTP/ATPDraw. Given the natural frequencies of a transmission line to which the proposed TCS (PTCS) is connected, it injects the appropriate frequencies and eliminates voltage oscillations which limit the use of TCS. To verify the efficiency of the PTCS, it is implemented in a real system with a shunt reactor, and the results are then compared with field measurements. A comparison of the results shows that the PTCS eliminates the voltage oscillations in the simulation before closing and provides a smooth voltage with the desired amplitude. Using the proposed model, the maximum line switching overvoltage is correctly calculated; this, in turn, results in a more accurate transmission line insulation design, which is technically and economically beneficial.